Characteristics Related to Parent-Child Literacy and Numeracy Practices in Preschool - Napoli, Amy R.; Korucu, Irem; Lin, Joyce; Schmitt, Sara A.; Purpura, David J. (Frontiers in Education, 2021)
Little research has been conducted to determine the factors that relate to the home literacy and numeracy environments within the same sample, despite their importance to children’s developing academic skills. These factors are important to investigate in order to determine what may foster or prevent parent-child engagement. The primary purpose of this study was to examine the shared and unique child and parent variables that are related to the frequency of parent-child literacy and numeracy practices. The 199 preschoolers included in the study ranged in age from 3.00 to 5.17 years (M = 4.16, SD = 0.57). Parents reported on child and family characteristics. Two multiple regression analyses were conducted (one each for home literacy and numeracy environments). Results indicated that parent and child characteristics were differentially related to the frequency of parent-child literacy and numeracy practices. Parents with higher levels of education engaged in significantly more literacy and numeracy activities with their children. Children’s age was related to parent-child literacy and numeracy activities. Parents’ beliefs of the importance of numeracy were positively associated with parent-child numeracy practices. In line with other research, parents reported finding literacy development to be more important than numeracy development and engaging in parent-child literacy practices more frequently than numeracy practices. Understanding factors that are related to the home literacy and numeracy environments may be an important step in identifying how to best encourage parents to engage their children in these practices at home.